1997
DOI: 10.1525/maq.1997.11.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Politics, Practical Logic, and Primary Health Care in Rural Haiti

Abstract: During the 1980s, an ambitious project for health development restructured medical services throughout rural Haiti. The "Rural Health Delivery System" (RHDS) pursued several goals of primary health care, including dispensary-based maternal and child health services and the provision of low-cost drugs. Based on fieldwork in a single village, this article examines how local residents pushed the project in unpredictable and ironic directions. People did not regard dispensary services-which were planned and financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Even if different medical practices exist on a single dimension, complementary or mutually renewing relationships are possible in a vertical or horizontal manner (Brodwin, 1997;Comaroff, 1980;Frank and Stollberg, 2004;Lock, 1984). In this vein, we expand two complementary models of cultural-institutional dynamics -i.e.…”
Section: Co-developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if different medical practices exist on a single dimension, complementary or mutually renewing relationships are possible in a vertical or horizontal manner (Brodwin, 1997;Comaroff, 1980;Frank and Stollberg, 2004;Lock, 1984). In this vein, we expand two complementary models of cultural-institutional dynamics -i.e.…”
Section: Co-developmentmentioning
confidence: 99%
“…Colonization has been substantially accompanied by the introduction of WAM into non-western colonies (Comaroff and Comoroff, 1992). Attempts to transform medical practices in the global South continue to this day, whether or not they are prompted by intentions equivalent to historical colonization projects (Brodwin, 1997;Reznik et al, 2007). In industrialized societies, conversely, efforts to revive TAM invoke both indigenous traditions and others' contemporary experience, such as acupuncture and Asian medical traditions (Bodeker, 2007;Bodeker and Burford, 2007;Frank and Stollberg, 2004;Mahady, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As political economic analyses of primary health care in the 1970s and 1980s demonstrated, national governments can shape or distort primary health care implementation to suit a variety of domestic agendas. However, as Brodwin (1997) argued, the intentions of both international funders and 25. Given the widely recognized aversion to the acknowledgement of sexuality across generations, it is likely that low adult attendance made Katleho Clinic more attractive to teenagers seeking contraceptive services.…”
Section: Conclusion: Uneven Transformations On Uneven Terrainmentioning
confidence: 99%
“…Despite the strong social justice content of PHC rhetoric, medical anthropologists reported that governments implemented these programs in ways that reflected and consolidated their own domestic agendas-whether these were directed toward political repression, economic liberalization, or revolutionary reform (see Morgan, 1989a and associated articles 2 ). Furthermore, the ultimate effects of PHC programs were shaped by local, as well as national, power relations and agendas (Brodwin, 1997).…”
Section: Introductionmentioning
confidence: 99%